Proof: Divide Simplify

Let's prove the following theorem:

if not (b = 0), then (bd) ⋅ (a / b) = da

Proof:

View as a tree | View dependent proofs | Try proving it

Given
1 not (b = 0)
Proof Table
# Claim Reason
1 (bd) ⋅ a = (da) ⋅ b (bd) ⋅ a = (da) ⋅ b
2 ((bd) ⋅ a) / b = ((da) ⋅ b) / b if (bd) ⋅ a = (da) ⋅ b, then ((bd) ⋅ a) / b = ((da) ⋅ b) / b
3 b / b = 1 if not (b = 0), then b / b = 1
4 ((da) ⋅ b) / b = (da) ⋅ (b / b) ((da) ⋅ b) / b = (da) ⋅ (b / b)
5 ((da) ⋅ b) / b = (da) ⋅ 1 if b / b = 1 and ((da) ⋅ b) / b = (da) ⋅ (b / b), then ((da) ⋅ b) / b = (da) ⋅ 1
6 (da) ⋅ 1 = da (da) ⋅ 1 = da
7 ((da) ⋅ b) / b = da if (da) ⋅ 1 = da and ((da) ⋅ b) / b = (da) ⋅ 1, then ((da) ⋅ b) / b = da
8 ((bd) ⋅ a) / b = da if ((da) ⋅ b) / b = da and ((bd) ⋅ a) / b = ((da) ⋅ b) / b, then ((bd) ⋅ a) / b = da
9 ((bd) ⋅ a) / b = (bd) ⋅ (a / b) ((bd) ⋅ a) / b = (bd) ⋅ (a / b)
10 (bd) ⋅ (a / b) = da if ((bd) ⋅ a) / b = da and ((bd) ⋅ a) / b = (bd) ⋅ (a / b), then (bd) ⋅ (a / b) = da

Comments

Please log in to add comments